The Didactic Potential of Edible Art Objects in the Development of Cultural Event Branding Strategies - Konstantinova-Hrendzha, Nataliia (Педагогічна Академія: наукові записки, 2026)
The active integration of artistic practices, gastronomy, and visual communication forms opens new opportunities for presenting cultural events and engaging audiences. One such phenomenon is food floristry and the creation of edible art objects from fruits and vegetables. Within the context of cultural events, these objects serve not only an aesthetic function but also become a means of conveying symbolic meanings and shaping emotional experience. The purpose of this study is to determine the didactic potential of edible art objects and to substantiate their role in developing cultural event branding strategies as a tool of visual communication. The study employs a set of methods. Analysis and synthesis of scholarly sources allowed the identification of the characteristics of food art and its place in the contemporary cultural environment. Cultural analysis was applied to interpret the symbolic content of edible sculptures. Case analysis facilitated the examination of the practical use of fruit art objects in international exhibition and commercial events. Observation enabled the delineation of the specific features of audiences’ emotional reception of the fusion of gastronomy and art. The findings establish that edible art objects possess significant didactic and communicative potential in the context of cultural events. Fruits and vegetables constitute an artistic medium with distinctive properties: natural texture, a diverse color palette, and a limited lifespan. The ephemeral nature of such objects intensifies emotional perception and generates a unique experience of engagement with the event. The combination of a gastronomic element and an artistic image creates a strong visual accent that is easily memorable and encourages further dissemination in the digital environment. Practical examples of fruit sculptures used at international exhibition and commercial events demonstrate their capacity to attract visitors’ attention, promote photography and the sharing of visual content, and foster positive associations with the event or brand. The conclusions indicate that edible art objects can be regarded as an effective tool of visual communication in cultural events, integrating art, gastronomy, and the emotional experience of the audience. Their use contributes to building a recognizable event identity, strengthening audience engagement, and expanding the creative representation of cultural meanings.